2018
DOI: 10.14202/vetworld.2018.642-648
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors associated with bulk tank milk urea nitrogen in Central Thailand

Abstract: Aim:The study was to determine seasonal fluctuations and non-nutritional factors associated with bulk tank milk urea nitrogen(BTMUN).Materials and Methods:A total of 58,364 BTM testing records were collected from 2364 farms in Central Thailand during September 2014-August 2015. Using square root BTMUN as the outcome, other milk components, farm effect, and sampling time were analyzed by univariable repeated measures linear regression, and significant variables were included in multivariable repeated measures l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
1
3
0
1
Order By: Relevance
“…Somatic cell counts in relation to MU confirmed a negative regression dependency in early (r = -0.635; P < 0.05) and mid lactation (r = -0.818; P < 0.05) but no significance was found in late lactation. These results are in agreement with previous reports by Kananub et al (2018) who confirmed the negative dependency between SCC and levels of MU, whereby this relationship explained as unclear forasmuch as those variables refer to physiological processes which are not clearly connected. Milk urea is related to the evaluation of protein nutrition in dairy cows and SCC reflects the degree of irritation in the mammary gland.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Somatic cell counts in relation to MU confirmed a negative regression dependency in early (r = -0.635; P < 0.05) and mid lactation (r = -0.818; P < 0.05) but no significance was found in late lactation. These results are in agreement with previous reports by Kananub et al (2018) who confirmed the negative dependency between SCC and levels of MU, whereby this relationship explained as unclear forasmuch as those variables refer to physiological processes which are not clearly connected. Milk urea is related to the evaluation of protein nutrition in dairy cows and SCC reflects the degree of irritation in the mammary gland.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies by Zhang et al (2018), who confirmed the negative dependency between milk protein and MU in dairy cows. Other studies examining this relationship did not find a significant correlation between these parameters (Kananub et al 2018). The lowest protein content in milk along with the over-the-limit MU level confirmed in a group of dairy cows in early lactation indicates a limited intake of amino acids from TMR.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the level of thiamine and xanthine is closely interrelated with that of AIR . In addition, the decrease of urea in milk from the CM group may be attributed to that most bacteria and fungi in the damaged udder area can produce urease to degrade urea in fresh milk . Orotic acid is synthesized in the mammary gland and is the only component of acid-soluble nucleotides in milk.…”
Section: Discussionmentioning
confidence: 57%
“…40 In addition, the decrease of urea in milk from the CM group may be attributed to that most bacteria and fungi in the damaged udder area can produce urease to degrade urea in fresh milk. 41 Orotic acid is synthesized in the mammary gland and is the only component of acid-soluble nucleotides in milk. It is a key intermediate for the synthesis of uridine by carbamate and aspartic acid.…”
Section: ■ Discussionmentioning
confidence: 99%
“…El NUL es un indicador importante y efectivo para establecer el estatus de nitrógeno ureico en vacas lecheras, pues esta herramienta permite identificar fácilmente una subalimentación o sobrealimentación de proteína (11,12). Su monitoreo es importante porque el NUL está relacionado con desórdenes de tipo reproductivo, e incremento de células somáticas, así como con un aumento en la excreción de nitrógeno con un impacto ambiental negativo (10,13,14,15). En Colombia, pocos estudios se relacionan con el análisis de NUL en rebaños lecheros (16,17), y con la variación del NUL con respecto a los días en leche (DEL) en las condiciones de clima tropical del país.…”
Section: Introductionunclassified